Ordered Au3Cu Nanocrystals Induced Phase Transformation in 2D-MoS2 as SERS Substrate for Enhancing Molecular Detection - Qamar U.; Mukherjee B.; Sasikala Devi A.A.; Das S. (My University, 2025)
Surface-enhanced Raman scattering (SERS) is one of the potent methods that provides remarkable sensitivity, selectivity, and adaptability for molecular analysis at an ultralow concentration level. Here, we report the synthesis of plasmonic ordered gold-copper alloy (Au3Cu) nanocrystals (NCs) with size ∼10 nm, which when dispersed over 2D-MoS2 resulted in light-induced phase transition from 2H-MoS2 (semiconducting) to 1T-MoS2 (metallic). The as-synthesized Au3Cu NCs showed a broad UV absorption and broad photoluminescence peak, along with a prolonged plasmonic decay. In Au3Cu NC-dispersed MoS2, a Schottky junction was formed, and upon light irradiation, the plasmonic hot electrons transferred from Au3Cu to MoS2, resulting in 2H to 1T phase transformation, thereby effectively strengthening the SERS signals. In this work, we demonstrate that the Au3Cu drop-casted MoS2 (Au3Cu/MoS2) substrates can be effectively used for the low-level detection of methylene blue (MB) and dopamine. These ordered Au3Cu NCs have homogeneous interparticle nanogaps that offer a stronger enhancement of electromagnetic field (EM) in turn, intensifying the generation of plasmons than the commonly used elemental gold or silver. We believe that the as-prepared Au3Cu-ordered NCs and their dispersion over MoS2 substrates can contribute to the development of Au3Cu/MoS2 systems with improved properties and plasmonic capacity, potentially opening up a wide range of opportunities for the creation of efficient SERS substrates for detecting even minute analyte concentrations. © 2024 American Chemical Society.